The gender perspective through the Novelas ejemplares. An example of the Critical Teaching and the Slow Teaching - Amores Bonilla, Pedro Antonio (Clio. History and History Teaching, 2019)
The current task tries to offer a possibility of tackling the gender perspective in 2nd level of ESO through by using the Novelas ejemplares by Cervantes and the Project Learning. All of this is tackled from the point of view of it’s possible to change the gender relationships through the critical teaching of the gender differencies as social and cultural constructs.